Ovulation and initial rearing of Steindachneridion parahybae (Siluriformes: Pimelodidae) larvae from different accumulated thermal units - Okawara, Renan Yoshiharu; Sanches, Eduardo Antônio; Caneppele, Danilo; Damasceno, Danielle Zanerato [UNESP]; Romagosa, Elizabeth (Springer Nature, 2015)
Steindachneridion parahybae is an endemic catfish to the Paraiba do Sul river basin classified as critically endangered. Little is known about the reproductive management of this species in captivity, adopting for this practice empirical measures. The objectives were to: (1) determine suitable Accumulated Thermal Units (ATUs) at the moment of ovulation in January 2011 and 2012; (2) follow initial larvae rearing in 180, 240 and 300 degree-hours. Nine selected females were divided into three experimental groups of three specimens each (replications), distributed at pre-established times: 140, 160, 180, 200, 220, 240, 260, 280 and 300 degree-hours. The females were induced with two doses of 0.5 and 5.0 mg kg−1 of dry carp pituitary, respectively, at an interval of 12 h. The extruded oocytes were kept at average water temperature of 22.35 ± 0.53 °C (2011) and 21.88 ± 0.15 °C (2012). Fertilization and hatching rates were: 84.22 and 71.33 % at 174.2 ATUs in 2011, and 55.58 % and 36.13 % at 251.0 ATUs in 2012. In January 2012, 900 larvae were distributed in three replications (triplicate) consisting of 100 larvae each and were fed: 120 (second day), 300 (third–fourth day), 600 (fifth–eighth day), and 1,200 Artemia salina nauplii per larva (ninth–15th day), six times a day. The larvae exhibited mean weight of 523.67 ± 54.42, 496.67 ± 61.98 and 475.00 ± 22.83 mg, length of 17.75 ± 0.57, 17.58 ± 0.51 and 17.45 ± 0.25 cm and survival of 63.95 ± 24.50, 71.71 ± 6.61 and 79.65 ± 0.82 %, when hatched in 180, 240 and 300 ATUs, respectively. The larvae body parameters did not show significant differences at these degree-hours.
Keywords: Degree-hours; Endangered fish species; Induced spawning; Larviculture; Temperature